Strategic Leadership and Organizational Success - "Mugo, Agnes M." (Nairobi)
Includes references
Keywords: "STRATEGIC LEADERSHIP;SERVANT LEADERSHIP;STRATEGIC MANAGEMENT;ORGANIZATION SUCCESS;LEADERSHIP-POST BANK, KENYA"